Catalysis by mont K-10 supported silver nanoparticles: a rapid and green protocol for the efficient ipso-hydroxylation of arylboronic acids. Issue 1 (1st January 2015) - Begum, Tahshina; Gogoi, Ankur; Gogoi, Pradip K.; Bora, Utpal
Graphical abstract: Abstract: A mild and efficient methodology has been developed for the ipso -hydroxylation of arylboronic acids using montmorillonite K-10 supported silver nanoparticles (AgNPs) as catalyst and aqueous H2 O2 as oxidant. The reactions were performed at room temperature within short reaction time under solvent- and base-free conditions. This catalyst shows good reusability.